Parameters Affecting the Thermodynamic Efficiency of PEM Single Cell and Stack of Cells (Two Cells) - Mohammed, Ghazwan Ahmed; Shneat, Amer Abdulkhader (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
In this work, thermodynamic efficiency of individual cell and stack of cells (two cells) has been computed by studying the variation of voltage produced during an operation time of 30 min as a result of the affected parameters:- stoichiometric feed ratio, flow field design on single cell and feed distribution on stack of cells. The experiments were carried out by using two cells, one with serpentine flow field and the other with spiral flow field. These cells were fed with hydrogen and oxygen at low volumetric flow rates from 1 to 2 ml/sec and stoichiometric ratios of fuel (H2) to oxidant (O2) as 1:2, 1:1 and 2:1 respectively. The results showed that the highest voltage and efficiency can be obtained for the stoichiometric ratio of 1:2, while the ratio of 2:1 produced the lowest voltage and efficiency. Also the best results were obtained with the serpentine flow pattern after comparing with the spiral flow pattern in a single cell. Likewise it was proved that the voltage and efficiency are maximized when using the stoichiometry of 1:2, besides that the parallel feed connection of the stack of cells produced much power than the series connection.